Perception of objective structured clinical examination and traditional practical examination in assessment of nursing students clinical competencies by nursing students in south west Nigeria - Idowu Edward, Mary; Okanlawon, Funmilayo (International Journal of Medical Research and Review, 2016)
Background: Clinical examination is a crucial part of nursing training programmes for assessing nursing student competencies which ultimately lead to the delivery of quality nursing care. Two methods of clinical assessment have been identified [Traditional Practical Examination (TPE) and Objective Structured Clinical Examination(OSCE)] in nursing and allied professions globally. Nursing and Midwifery Council of Nigeria (N&MCN) had always used TPE for all clinical examinations in nursing but adopted OSCE two decades ago for only midwifery examination while the examination in general nursing still remains TPE. There is dearth of literature on the perception of these two methods in Nigeria hence this study. This will help to determine best preferred method for clinical assessment among nursing students in Nigeria. Methods: The study utilised one-group quasi experimental design. Two Hospital-based and two University-based nursing schools randomly selected in South-west Nigeria participated in the study. Purposive sampling technique was used to select 187 nursing students out of which 157 participated in the study. T-test, ANOVA and chi-square were used to analyze the data at 0.05level of significance. Results: Significant difference existed between the mean scores of the two practical examinations: TPE 59.31+2.92, OSCE 64.59+5.15, t=3.29, p=0.002. OSCE was perceived to be more objective compared to TPE, p=0.000, consume less time p=0.010, assessed wider range of learned materials, p=0.000, less destabilizing during practical session, p=0.001, less stressful p=0.002. Perception on which method demands more preparation showed no significant difference between OSCE and TPE, p=0.097. Lastly, 56.8% of participants preferred OSCE to TPE, p=0.001. Conclusion: OSCE is perceived to be a better method than TPE. It is recommended that OSCE should be adopted as method of practical examination for nursing training programmes in Nigeria.